Wheelchair Controlled by Eye Movement Using Raspberry Pi for ALS Patients - Buele, Jorge (2020)
The mobility of people who have suffered a degenerative disease or an accident is partially or totally reduced, which limits their locomotive independence. Therefore, this paper presents a proposal that facilitates the mobility of people suffering from moderate levels of amyotrophic lateral sclerosis (ALS). A control system has been adapted to an electric wheelchair to provide it with a certain degree of intelligence. The acquisition of multimedia data is done with a small camera adapted to a glasses frame that the person must use. For eye patterns tracking, a recognition system is performed using the LabVIEW software environment. The control system that regulates the movement of the wheelchair was designed on the Raspberry Pi embedded board as a low-cost proposal. Experimental tests and user surveys validate the correct operation of this device. © 2020, Springer Nature Switzerland AG.